Microbial response on the first full-scale DEMON® biomass transfer for mainstream deammonification. (30th June 2022) - Podmirseg, Sabine Marie; Gómez-Brandón, María; Muik, Markus; Stres, Blaz; Hell, Martin; Pümpel, Thomas; Murthy, Sudhir; Chandran, Kartik; Park, Hongkeun; Insam, Heribert; Wett, Bernhard
Highlights: Anammox monitoring via heme quantification, particle tracking and molecular tools. Anammox biomass retention successfully achieved in the mainstream. Bioaugmentation of AOB and competition of Nitrobacter and Nitrospira observed. Switch in activity pattern led to simultaneous ammonia and nitrite depletion. Repression of nitrite oxidation witnessed in the mainstream. Abstract: Sidestream partial nitritation and deammonification (pN/A) of high-strength ammonia wastewater is a well-established technology. Its expansion to the mainstream is, however mainly impeded by poor retention of anaerobic ammonia oxidizing bacteria (AnAOB), insufficient repression of nitrite oxidizing bacteria (NOB) and difficult control of soluble chemical oxygen demand and nitrite levels. At the municipal wastewater treatment plant in Strass (Austria) the microbial consortium was exhaustively monitored at full-scale over one and a half year with regular transfer of sidestream DEMON® biomass and further retention and enrichment of granular anammox biomass via hydrocyclone operation. Routine process parameters were surveyed and the response and evolution of the microbiota was followed by molecular tools, ex-situ activity tests and further, AnAOB quantification through particle tracking and heme measurement. After eight months of operation, the first anaerobic, simultaneous depletion of ammonia and nitrite was observed ex-situ, together with a direction to higher nitrite generation (68% of total NOx -N) as compared to nitrate under aerobic conditions. Our dissolved oxygen (DO) scheme allowed for transient anoxic conditions and had a strong influence on nitrite levels and the NOB community, where Nitrobacter eventually dominated Nitrospira . The establishment of a minor but stable AnAOB biomass was accompanied by the rise of Chloroflexi and distinct emergence of Chlorobi, a trend not seen in the sidestream system. Interestingly, the most pronounced switch in the microbial community and noticeable NOB repression occurred during unfavorable conditions, i.e. the cold winter season and high organic load. Further abatement of NOB was achieved through bioaugmentation of aerobic ammonia oxidizing bacteria (AerAOB) from the sidestream-DEMON® tank. Performance of the sidestream pN/A was not impaired by this operational scheme and the average volumetric nitrogen removal rate of the mainstream even doubled in the second half of the monitoring campaign. We conclude that a combination of both, regular sidestream-DEMON® biomass transfer and granular SRT increase via hydrocyclone operation was crucial for AnAOB establishment within the mainstream. Graphical abstract: Image, graphical abstract